Image Quality Comparison of Filter Placement Effect on the LWIR Camera of LAPAN A4 Satellite - Hartono, Rommy; Dede Ardianto; Syafrudin, A. Hadi (Indonesian Journal of Aerospace, 2024)
The LAPAN A4 LWIR camera has already been installed with a bandpass filter, generating a spectral response whose value is near the spectral response of TIRS bands 10 and 11 of LANDSAT 8. Due to the small size of the mechanical part of the LWIR bandpass filter, which has a diameter of 32.5mm, a problem arises when installing the LWIR filter. The filter can be placed in four different positions inside the LWIR camera, and these four positions are also viable for capturing images. This paper aims to compare images generated from four possible filter placements on the LWIR camera using the LAPAN LWIR filter to obtain the best image quality from the LAPAN LWIR camera. To achieve optimal results from these four possible placements, statistical analyses such as standard deviation, SNR calculation, dynamic range, and spatial response area using a moving average filter are employed to assess image quality. Based on the tests and the analysis of signal-to-noise ratio and dynamic range, filter placements behind the zoom lens and in front of the focus lens are nearly identical and superior to those in front of the zoom lens and behind the focus lens. Conversely, the analysis of spatial response area using a moving average filter shows that the filter in front of the zoom and focus lens is superior to that behind the zoom lens. Therefore, the recommendation is to place the filter in front of the zoom and focus lens for the final assembly